2020
DOI: 10.21203/rs.3.rs-24637/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical efficacy and safety in patients treated with teicoplanin with a target trough concentration of 20 μg/mL using a regimen of 12 mg/kg for five doses within the initial 3 days

Abstract: Background: A trough concentration (Cmin) ≥20 μg/mL of teicoplanin is recommended for the treatment of serious methicillin-resistant Staphylococcus aureus (MRSA) infections. However, sufficient clinical evidence to support the efficacy of this target Cmin has not been obtained. Even though the recommended high Cmin of teicoplanin was associated with better clinical outcome, reaching the target concentration is challenging.Methods: Pharmacokinetics and adverse events were evaluated in all eligible patients. For… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Ninety‐three articles, including studies that did not assess the target trough concentration range of 15–30 μg/ml (cut‐off value of 13 [1] or 20 μg/ml [3]). We finally included four articles ( n = 299) that assessed clinical efficacy 31‐34 and three articles ( n = 546) 32‐34 that assessed adverse effects in the meta‐analysis. No RCTs have assessed the associations of the target trough concentration of teicoplanin with efficacy and safety.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ninety‐three articles, including studies that did not assess the target trough concentration range of 15–30 μg/ml (cut‐off value of 13 [1] or 20 μg/ml [3]). We finally included four articles ( n = 299) that assessed clinical efficacy 31‐34 and three articles ( n = 546) 32‐34 that assessed adverse effects in the meta‐analysis. No RCTs have assessed the associations of the target trough concentration of teicoplanin with efficacy and safety.…”
Section: Resultsmentioning
confidence: 99%
“…13 Byrne et al found that although their hospital adopted higher than conventional doses for patients with haematological malignancy with the aim of achieving a trough concentration approximately 50 kg) using a regimen of five doses of 600 mg every 12 h. 33 They also reported that five doses of 12 mg/kg teicoplanin delivered at 12-h intervals were required to achieve a target trough concentration of ≥20 μg/ml in patients with difficult MRSA infections. 34 Ramos-Martin et al reported that an AUC/MIC ratio of 610.4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations